Exploring the challenges of unmarried pregnancy among adolescents: a comprehensive literature review - Mohamad Fakhryamin, Yasmeen Nursyaqira; Mohd Khir, Azlina; Md Noor, Amna (Human Resources Management Academic Research Society (HRMARS), 2024)
Adolescent pregnancy, particularly outside of marriage, is a significant issue in Malaysia, impacting the lives of young women and posing various challenges. This article reviews the scope of unwed pregnancies among adolescents in Malaysia, analysing data from the Ministry of Health and other sources to highlight the prevalence and trends of this issue. It identifies key factors contributing to teenage pregnancies, including weak family relationships, socioeconomic status, and peer influence. The article discusses the multifaceted challenges faced by pregnant teenagers, including family acceptance, social stigma, effects on physical health, financial difficulty, academic disturbance, and effects on psychological well-being. Additionally, it explores coping mechanisms employed by adolescents and the role of social support from family, institutions, and the community. The study highlights the critical need for all-encompassing approaches to combat adolescent pregnancy, such as enhanced sex education, easier access to reproductive health care, and supporting measures to lessen the harmful consequences on teenagers. The results highlight how crucial it is for everyone to provide support and work together to guide the adolescents and offer the required assistance to lower the number of adolescent pregnancies and improve the lives of those who are impacted.